Correction to: Consecutive-Day Ventricular and Atrial Cardiomyocyte Isolations from the Same Heart: Shifting the Cost–Benefit Balance of Cardiac Primary Cell Research (Cells, (2022), 11, 2, (233), 10.3390/cells11020233) - Greiner, Joachim; Schiatti, Teresa; Kaltenbacher, Wenzel; Dente, Marica; Semenjakin, Alina; Kok, Thomas; Fiegle, Dominik; Seidel, Thomas; Ravens, Ursula; Kohl, Peter; Peyronnet, Rémi; Rog-Zielinska, Eva A. (Cells, 2024)
In the original publication [1], there was an error in the Materials and Methods Section, Sub-Section 2.3. Cell Isolation. The concentration of the digestion solution was wrong. The correct concentration appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. Tissue was then rinsed twice in wash solution 1 (each 2 mL), and further digested with Liberase TL Research Grade (concentration: 0.23 mg/mL in 2.2 mL wash solution 1 supplemented with 5 µM CaCl2; Hoffmann-La Roche, Basel, Switzerland) for up to 45 min (ventricles)/15 min (atria).
CRIS-Team Scopus Importer:2024-07-12